Complications and oncologic outcome in bladder cancer patients receiving radical cystectomy after intravesical instillation treatment - Lisa J. Frey; Katarzyna E. Banasiewicz; Christian Ruckes; Isabel Wagner; Maximilian Haack; René Mager; Eva Juengel; Axel Haferkamp; Gregor Duwe; Maximilian P. Brandt (PLoS ONE, 2025)
Objective To evaluate the impact of previous intravesical treatment with Bacillus Calmette-Guérin (BCG) or mitomycin on postoperative complications and oncologic outcome in non-muscle invasive bladder cancer (NMIBC) patients receiving radical cystectomy (RC). Patients and methods Between 2016 and 2021, 366 patients who received RC for bladder cancer (BC) were screened. Patients with intravesical treatment with either BCG or mitomycin for NMIBC were compared to patients with BC without prior intravesical treatment. Patients were matched manually for ASA-score, BMI cluster, age, and sex. TNM stages were used as covariates in the analysis model. All complications within 30 days post-surgery and the 90-day mortality rates were analyzed. Patient characteristics were compared between groups using Chi 2 -tests, and associations were evaluated by logistic regression. Firth logistic regression was applied for comorbidities. Kaplan–Meier curves were generated for overall survival (OS) and progression-free survival (PFS), and Cox regression analysis was performed to further assess survival outcomes. Results We identified 51 matched patients receiving BCG or mitomycin for NMIBC. Nine women and 42 men were in the interventional group with a mean age of 70 and a BMI of 27.6. In both groups, ASA-score 2, 3, and 4 were present in 18, 29, and four patients. According to the Clavien–Dindo (CD) classification grade ≥ 3b, neither the incidence nor severity of complications differed significantly between groups. Final histopathology and survival outcomes (OS, PFS) were comparable. No associations were found between complications and urinary diversion or surgical approach. As expected, advanced T- and N-stages correlated with worse survival, while coronary artery disease (CAD) was significantly associated with postoperative complications. Conclusions To our knowledge, this is the first matched pair analysis that evaluates the impact of intravesical treatment on postoperative complications for patients with NMIBC receiving RC. Intravesical treatment with BCG or mitomycin did not deteriorate postoperative complications in NMIBC patients after RC, irrespective of the final histopathology stage. Oncologic outcomes were similar in both groups.